Construction of university faculty timetables using logic programming techniques - Fahrion, Roland; Dollansky, Gerhard (Discrete applied mathematics, 1992)
A Prolog rule system for timetable construction in university faculties is proposed. The main module is concerned to the search of feasible instructor/room assignments under additional consideration of the faculty's education plan and certain a priori fixed assignment options. For accelerating the assignment search, a simple heuristic priority scheme is assumed. In another module, manual procedures for manipulating interactively the assignment results are possible. Further modules control the menu-driven input and maintenance of room and time planning data, manage the creation of timetable outputs and numerous survey tables, and thus contribute to a high transparency of the timetable planning process. The conceptional scheme of the underlying database contains information about lectures, exercises and seminars, lecturers and instructors, lecture halls, exercise rooms, and equivalent compatible rooms. Practical experiences with the program system, run on At microcomputers, will be reported.
Available online 20 May 2002
Gesehen am 31.10.2024